« Do we really need a dam ? » Le conflit lié au barrage Gordon-below-Franklin (Tasmanie, Australie) ou la redéfinition d’un cycle hydrosocial ? - Silvia Flaminio (Développement Durable et Territoires)
This article focuses on opposing and abandoning the Gordon-below-Franklin dam project (Tasmania, Australia). The project had been put forward by the Hydro-Electric Commission of Tasmania towards the end of the 1970s. The article analyses more specifically how the hydraulic fix which the project represents is debated in the public sphere and how the utility and the efficiency of the technical infrastructure is contested. Abandoning the hydraulic infrastructure project leads to the redefinition of its hydrocracy and plays a role in the disintegration of a technical hydrosocial cycle. Nevertheless, a green hydrosocial cycle is only partially produced during and after the controversy.